Odpowiedzi

2009-11-13T15:39:19+01:00
A)
2x+3y=5(x-3)
4(x+5)-2(y-3)=34

2x+3y=5x-15
4x+20-2y+6=34

2x-5x=-3y-15
4x+20-2y+6=34

-3x=-3y-15 I:-3
4x+20-2y+6=34

x=y+5
4(y+5)+20-2y+6=34

x=y+5
4y+20+20-2y+6=34

x=y+5
4y-2y=34-20-20-6

x=y+5
2y=-12 I:2

x=y+5
y=-6

x=-6+5
y=-6

x=-1
y=-6


b)
y/3-x/4+1/3=1/2 I*12
y/4-5/8=-x/3-1/2 I*24

12*y/3-12*x/4+12*1/3=12*1/2
24*y/4-24*5/8=-24*x/3-24*1/2

4y-3x+4=6
6y-15=-8x-12

4y-3x=2
6y+8x=3

4y=3x-2 I:4
6y+8x=3

y=¾x-½
6(¾x-½)+8x=3

y=¾x-½
4½x-3+8x=3

y=¾x-½
12½x=6 I:12½

y=¾x-½
x=0,48

y=¾*0,48-½
x=0,48

y=0,36-½
x=0,48

y=-0,14
x=0,48


c)
4(2a-b)/3+b/2=1/2(a-b)+8+2(a+b)/3
-1+3-b/4=a+1/3

8a-4b/3+b/2=½a-½b+8+2a+2b/3
2-b/4=a+⅓
2009-11-13T16:41:24+01:00
A)2x+3y=5(x-3)
4(x+5)-2(y-3)=34

2x+3y=5x-15 /(-2)
4x+20-2y+6=34

-4x-6y=-10+30
4x+20-2y+6=34

-4x-6y=20
4x-2y=34-20-6

-4x-6y=20
4x-2y=8

4y=12 /:4
y= 3


4x-2y=8
4x-2*3=8
4x-6=8
4x=8+6
4x=14 /:4
x= 14/4= 3,5